Analisis Rendahnya Minat Masyarakat Terhadap Pelaporan Praktek Vote Buying - Sinaga, Etro Jaya; Maryanah, Tabah (Journal of Government and Social Issues (JGSI), 2022)
Elections are a means of implementing the people's sovereignty to directly, generally, freely, secretly, honestly, and fairly choose their leaders. However, elections based on honesty seem to still not be categorized as perfect honesty. The existence of vote buying practices in the Lebong Regency area indicates that there is a need for system improvement to overcome problems that always arise in every election. This study focuses on knowing the interest of the Lebong Regency community in combating election crimes, especially vote buying, by giving cash to voters. The respondents for this study were 10 people who received money and those who did not receive money during the 2019 election and the 2020 regional election, as well as the Campaign Team of one of the participants in the 2019 election and the 2020 regional election. Additionally, this study also involved members of the Lebong Regency Election Supervisory Agency (Bawaslu) to strengthen the author's argument. The research method used descriptive qualitative methods with data collection based on interviews and information from informants. The results of this study indicate that habits, kinship, economy, reward, legal certainty, and political education influence a person's interest in reporting election crimes, especially vote buying.